Improvements in Bladder Function Following Activity-Based Recovery Training With Epidural Stimulation After Chronic Spinal Cord Injury - Herrity, April N.; Aslan, Sevda C.; Ugiliweneza, Beatrice; Mohamed, Ahmad Z.; Hubscher, Charles H.; Harkema, Susan J. (Frontiers in Systems Neuroscience, 2021)
Spinal cord injury (SCI) results in profound neurologic impairment with widespread deficits in sensorimotor and autonomic systems. Voluntary and autonomic control of bladder function is disrupted resulting in possible detrusor overactivity, low compliance, and uncoordinated bladder and external urethral sphincter contractions impairing storage and/or voiding. Conservative treatments managing neurogenic bladder post-injury, such as oral pharmacotherapy and catheterization, are important components of urological surveillance and clinical care. However, as urinary complications continue to impact long-term morbidity in this population, additional therapeutic and rehabilitative approaches are needed that aim to improve function by targeting the recovery of underlying impairments. Several human and animal studies, including our previously published reports, have documented gains in bladder function due to activity-based recovery strategies, such as locomotor training. Furthermore, epidural stimulation of the spinal cord (scES) combined with intense activity-based recovery training has been shown to produce volitional lower extremity movement, standing, as well as improve the regulation of cardiovascular function. In our center, several participants anecdotally reported improvements in bladder function as a result of training with epidural stimulation configured for motor systems. Thus, in this study, the effects of activity-based recovery training in combination with scES were tested on bladder function, resulting in improvements in overall bladder storage parameters relative to a control cohort (no intervention). However, elevated blood pressure elicited during bladder distention, characteristic of autonomic dysreflexia, was not attenuated with training. We then examined, in a separate, large cross-sectional cohort, the interaction between detrusor pressure and blood pressure at maximum capacity, and found that the functional relationship between urinary bladder distention and blood pressure regulation is disrupted. Regardless of one’s bladder emptying method (indwelling suprapubic catheter vs. intermittent catheterization), autonomic instability can play a critical role in the ability to improve bladder storage, with SCI enhancing the vesico-vascular reflex. These results support the role of intersystem stimulation, integrating scES for both bladder and cardiovascular function to further improve bladder storage.